A STUDY OF MICRO AND SMALL ENTERPRISES IN MANADO - Mogontha, Demita (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2013)
Small and Medium Enterprises (SMEs) is the backbone and fundamental base to build and sustain the economy of Indonesia. Small and Medium Enterprises have so many benefits and play a major role but in the other side, micro and small enterprises in Indonesia are facing many problems and challenges related to the characteristic of SMEs. To develop the economic welfare of a city, finding out the challenges and problems also to identify success factor are very important. This research was held in Manado as a developing city in Indonesia with 9 Micro and Small Enterprises that have excellent products and services as the samples. Qualitative research is deployed and using exploratory research to define the nature of Micro and Small Enterprises in Manado and using Descriptive-Study Case approach. Data and process triangulation are used to check the validity. The results of this research shows marketing & promotion, human resources & structure of the firm, technology & capital, product & services, financial resources, external environment and entrepreneurial readiness are the success factors while limited resources, mastery of Information & Technology, marketing, business license & legality, and labors become the challenges and problems of Micro and Small Enterprises in Manado. Keywords: micro and small enterprises, success factors, problems and challenges